2005
DOI: 10.1038/sj.ejcn.1602334
|View full text |Cite
|
Sign up to set email alerts
|

Restricted intraindividual urinary iodine concentration variability in nonfasting subjects

Abstract: Objective: Individual urinary iodine concentration (UIC) reflects iodine intake over a short time prior to sampling. Since eating habits are relatively constant in single subjects, UIC should be relatively constant in a given individual. The aim of our study was to verify this hypothesis by assessing UIC in repeated single urine samples from a group of healthy subjects. Design and Setting: A prospective sequential investigation was performed in 131 volunteer health workers or students recruited in our Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…This probably reflects a higher intake of sodium associated with food, in men, because their mean BMI, weight and height, besides sodium urinary excretion, were higher than in women. In other studies, mean UI excretion was also higher in men [8,9,21] , or similar in both genders, being not significant, but higher, in women in the work of Busnardo et al [12] and associated with body weight in the study of Vanacor et al [10] . As body weight is closely associated with gender, it is difficult to separate the impact of each of them in the excretion of UI.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This probably reflects a higher intake of sodium associated with food, in men, because their mean BMI, weight and height, besides sodium urinary excretion, were higher than in women. In other studies, mean UI excretion was also higher in men [8,9,21] , or similar in both genders, being not significant, but higher, in women in the work of Busnardo et al [12] and associated with body weight in the study of Vanacor et al [10] . As body weight is closely associated with gender, it is difficult to separate the impact of each of them in the excretion of UI.…”
Section: Discussionmentioning
confidence: 88%
“…The variability of UI excretion in the same individual has been estimated, in the majority of studies, from spot urine samples, disregarding the variability of UI excretion during a day [7,8,[11][12][13][14] . As food ingested over the weekend can be different from the one ingested on the other days, the objective of this study was to evaluate the variability of 24-hour UI excretion intra-and interindividually on 3 days of a week, including Sunday, in healthy subjects, living in Southern Brazil, and the correlation among the urinary excretion of iodine and sodium.…”
mentioning
confidence: 99%
“…In contrast to some studies [4,7,9], but in agreement with others [1,19], we defined UI by ICR. A couple of studies [8,28] advised against the use of ICR since it may underestimate UI concentrations compared to 24-hour urine and overestimate iodine concentrations in women compared to men.…”
Section: Discussionmentioning
confidence: 41%
“…Rasmussen et al [1] suggested avoiding non-fasting samples in the morning since UI excretion concentrations seemed to be lowest then. In contrast, Busnardo et al [9] reported only small variations in UI excretion concentrations in non-fasting subjects. Taking the time of sampling into account, the main results of our analyses did not substantially change.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation